Intuitive Design Thinking Criteria of Designers in Problem Solving - Zainudin Siran; Rusmadiah Anwar; Mohd Hafizuddin Mohd Yusof (Wacana Seni Journal of Arts Discourse, 2025)
Industries involved in research and development for new product development (NPD) typically employ experts from various disciplines and knowledge domains, including engineering design, art-based design, interface design, information technology, and more. These differences in discipline and experience influence the approaches and solutions taken when addressing problems in NPD projects, such as functionality, aesthetics, usability, manufacturing, and so on. For this reason, an in-depth study was conducted to explore intuitive design thinking behaviour across different knowledge domains. The study employed an empirical method involving the observation of experimental design and Design Protocol Analysis (DPA), conducted with the participation of 30 final-year undergraduate students who were divided into three groups: engineering design (ENG), art-based design (IDE), and interface design (ID). Besides profiling the intuitive design thinking behaviours of these three domain groups, findings also revealed distinct patterns in problem solving whereby ENG participants emphasised usability with less focus on aesthetics; IDE participants prioritised aesthetics with less emphasis on usability; and ID participants balanced both ergonomic and aesthetic considerations. Based on these findings, the researchers proposed a new model for design management within organisations that employ multidisciplinary designers. This model is intended to enhance the quality of operations in the NPD process and to shorten project durations by reducing repetitive processes caused by rejections at different stages of development.